Liquid metal-based electromagnetic shielding flexible coaxial fiber and method of making same
Patent Information
- Application Number
- CN202512042684.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-31
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-12-31
AI Technical Summary
[0004]然而,当前针对柔性电子织物的电磁屏蔽解决方案仍存在诸多技术缺陷,难以满足上述综合需求
[0017]因此,本发明采用上述的一种液态金属基电磁屏蔽柔性同轴纤维及其制备方法,制备得到的三层同轴结构形成了协同效应,其中,内层液态金属芯层中的镓铟合金作为低熔点液态金属,具有优异的导电性,支持高速信号传输,不仅能快速导走入射电磁波,还可对未导走的电磁波进行初步吸收,能适应柔性电路的构建需求,从而大大提高结构的可靠性和适用性;中层高聚物隔离层中的SEBS作为柔性绝缘高分子,一方面可避免内层液态金属与外层银纳米片复合层直接接触导致的导电干扰,另一方面能阻挡部分穿透内层的电磁波,形成二次隔绝;外层银纳米片复合层中银纳米片的高比表面积使其具备优异的电磁波反射能力,能够提供优异的电磁屏蔽效果,有效防止外界电磁波的干扰,并能保持优异的机械性能与可穿戴性。高聚物隔离层的存在,让液态金属芯的柔性和传输性能不受银纳米片复合层影响,同时保护液态金属不泄露或氧化。银纳米片复合层的机械性能,支撑液态金属芯的柔性结构在动态使用中不轻易损坏,保障长期稳定性。液态金属的柔性与银纳米片的机械稳定性,让纤维既能适应人体活动的动态场景,又不易断裂;信号传输和电磁屏蔽的协同,让纤维既能作为可穿戴设备的信号载体,又能避免外界电磁波干扰。
Smart Images

Figure CN121737871B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electromagnetic shielding fiber technology, and in particular to a liquid metal-based electromagnetic shielding flexible coaxial fiber and its preparation method. Background Technology
[0002] In recent years, with the rapid development of electronic technology, materials science, and flexible manufacturing processes, wearable electronic devices have gradually evolved from rigid structures to flexible and fibrous designs, forming a new form of electronic product—flexible wearable electronic fabrics. Flexible electronic fabrics achieve seamless integration of electronic devices with the human body and clothing by integrating functional components such as sensors, power supply, data storage, and wireless communication into a fiber or fabric substrate. For example, smart ECG monitoring clothing can achieve long-term, non-invasive ECG signal recording by integrating conductive fibers and electrodes, which is helpful for the early screening of diseases such as arrhythmia and cardiomyopathy.
[0003] Wearable electronic fabrics have shown great potential in the field of physiological signal monitoring. However, due to the low amplitude and low power characteristics of human physiological signals, they are highly susceptible to environmental electromagnetic interference, which reduces the accuracy and reliability of signal measurement and increases the difficulty of signal acquisition and analysis. For example, the amplitude of electrocardiogram (ECG) signals is between 0.1-5mV, making them susceptible to power frequency interference and electromagnetic radiation from wireless communication devices, leading to baseline drift and signal distortion. Therefore, improving the electromagnetic shielding performance of wearable electronic fabrics and reducing the impact of the external environment on physiological signal detection is an important technical approach to improve measurement accuracy and device reliability. Furthermore, since wearable devices need to be in contact with human skin for extended periods, the materials must possess high flexibility, good breathability, and skin compatibility to avoid skin discomfort or restricted movement caused by prolonged wear. Large-scale applications require material preparation processes with stable parameters, controllable procedures, and easy mass production, and the products must maintain structural durability during long-term use, such as maintaining stable performance after stretching, bending, and washing.
[0004] However, current electromagnetic shielding solutions for flexible electronic fabrics still suffer from numerous technical shortcomings, making it difficult to meet the aforementioned comprehensive requirements. One method, fiber coating, achieves shielding by coating ordinary fibers with a metal film or carbon-based composite material. However, this method suffers from weak adhesion between the coating and the fiber substrate, leading to coating peeling after prolonged wear and friction, resulting in decreased shielding performance. Furthermore, the brittleness of the metal coating limits fiber flexibility, and the coating can clog fiber pores, severely reducing fabric breathability. Another method, composite fiber processing, involves blending conductive particles with a polymer matrix to create fibers. However, this method suffers from the tendency of conductive particles to agglomerate, requiring increased addition to maintain shielding effectiveness. High addition amounts, however, reduce fiber flexibility and result in a stiff feel. Additionally, the shielding effectiveness of carbon-based particles is largely limited to the low-frequency band, failing to cover the mid-frequency bands commonly used in wearable devices. High-frequency bands have poor compatibility with shielding frequency bands; the textile material body conductivity method embeds electromagnetic shielding fibers into the fabric structure through textile processes, but it faces the problem of poor compatibility between fibers and fabric weaving, which easily damages the flexibility and extensibility of the fabric. Moreover, the uniformity of the distribution of shielding fibers is highly dependent on the weaving process, making it difficult to achieve uniform shielding across the entire area, resulting in signal interference vulnerabilities. At the same time, the process is complex and the production cost is high, which is not conducive to large-scale mass production; although the traditional layered structure method attempts to integrate shielding functions through multi-layer structures, it mostly adopts the design concept of rigid polymer substrate and single conductive layer, lacking interlayer synergy, and cannot meet the requirements of high shielding effectiveness, low weight, and high flexibility, making it difficult to adapt to the usage requirements of wearable scenarios.
[0005] Therefore, it is evident that the electromagnetic shielding fibers currently available cannot simultaneously meet the comprehensive requirements of flexible electronic fabrics for wide-band high electromagnetic shielding effectiveness, high flexibility, wearability, structural durability, and large-scale production. This has become a core technological bottleneck restricting the performance improvement of flexible wearable physiological signal monitoring devices. Summary of the Invention
[0006] The purpose of this invention is to provide a liquid metal-based electromagnetic shielding flexible coaxial fiber and its preparation method to solve the above-mentioned problems.
[0007] This invention provides a liquid metal-based electromagnetic shielding flexible coaxial fiber. The flexible coaxial fiber has a three-layer coaxial structure, consisting of a liquid metal core layer, a polymer isolation layer, and a silver nanosheet composite layer from the inside out. The liquid metal core layer is made of a liquid metal composite material formed by blending SEBS solution with gallium indium alloy and then curing it through solvent evaporation. The polymer isolation layer is composed of an SEBS matrix formed by completely evaporating the SEBS solution with toluene. The silver nanosheet composite layer is made of a silver nanosheet composite material formed by blending SEBS solution with silver nanosheets and then curing it through solvent evaporation. The overall diameter of the flexible coaxial fiber is 3.35 ± 0.05 mm.
[0008] A method for preparing the liquid metal-based electromagnetic shielding flexible coaxial fiber as described above is provided, comprising the following steps: S1. Prepare SEBS matrix material. Place the SEBS matrix material in a dry environment and dry it for 10 hours to remove residual moisture from the material and avoid bubbles from forming during subsequent dissolution and blending processes. S2. Add the dehydrated SEBS matrix material from step S1 and toluene into a container, place the container at 60°C, and stir continuously with a stirring device until the SEBS particles are completely dissolved to obtain a SEBS solution. S3. Take the SEBS solution obtained in step S2 and mix it with the silver nanosheets. Then, mechanically stir and blend the mixture to obtain a silver nanosheet composite material with uniformly dispersed silver nanosheets. S4. Take the SEBS solution obtained in step S2 and mix it with gallium indium alloy. Mechanically stir and blend the mixture to obtain a liquid metal composite material with uniformly dispersed gallium indium alloy. S5. The silver nanosheet composite material obtained in step S3, the SEBS solution obtained in step S2, and the liquid metal composite material obtained in step S4 are respectively fed into a coaxial extrusion device to extrude and obtain pre-formed coaxial fibers. S6. The coaxial fiber initially formed in step S5 is heated in an environment of 60°C to accelerate the evaporation of toluene solvent. After the solvent has completely evaporated, liquid metal-based electromagnetic shielding flexible coaxial fiber is obtained.
[0009] Preferably, in the above-mentioned method for preparing a liquid metal-based electromagnetic shielding flexible coaxial fiber, the drying environment in step S1 is a drying oven, and the temperature inside the drying oven is controlled between room temperature and 60°C.
[0010] Preferably, in the above-mentioned method for preparing a liquid metal-based electromagnetic shielding flexible coaxial fiber, the mass ratio of the SEBS matrix material to toluene in step S2 is 1:3.
[0011] Preferably, in the above-mentioned method for preparing a liquid metal-based electromagnetic shielding flexible coaxial fiber, the stirring speed in step S2 is controlled at 150-300 rpm, and stirring is continued for 24 hours to ensure that the SEBS particles are fully dissolved and the solution is uniform.
[0012] Preferably, in the above-mentioned method for preparing a liquid metal-based electromagnetic shielding flexible coaxial fiber, the volume ratio of the SEBS solution to the silver nanosheet in step S3 is 5:1, and the diameter of the silver nanosheet is 5-10 micrometers.
[0013] Preferably, in the above-mentioned method for preparing a liquid metal-based electromagnetic shielding flexible coaxial fiber, the duration of mechanical stirring and mixing in step S3 is 3 minutes, and the stirring speed is 180-220 rpm to avoid agglomeration of the silver nanosheets.
[0014] Preferably, in the above-mentioned method for preparing a liquid metal-based electromagnetic shielding flexible coaxial fiber, the volume ratio of SEBS solution to gallium indium alloy in step S4 is 1:1.
[0015] Preferably, in the above-mentioned method for preparing a liquid metal-based electromagnetic shielding flexible coaxial fiber, the duration of mechanical stirring and mixing in step S4 is 5 minutes, and the stirring speed is 180-220 rpm.
[0016] Preferably, in the above-mentioned method for preparing a liquid metal-based electromagnetic shielding flexible coaxial fiber, the extrusion speed of the coaxial extrusion device in step S5 is 1.2-1.6 mm / min.
[0017] Therefore, this invention employs the aforementioned liquid metal-based electromagnetic shielding flexible coaxial fiber and its preparation method. The resulting three-layer coaxial structure exhibits a synergistic effect. The gallium-indium alloy in the inner liquid metal core layer, as a low-melting-point liquid metal, possesses excellent conductivity, supporting high-speed signal transmission. It can not only quickly guide incident electromagnetic waves but also preliminarily absorb unguided electromagnetic waves, adapting to the construction requirements of flexible circuits and thus greatly improving the reliability and applicability of the structure. The SEBS in the middle polymer isolation layer, as a flexible insulating polymer, avoids conductive interference caused by direct contact between the inner liquid metal and the outer silver nanosheet composite layer, and also blocks some electromagnetic waves penetrating the inner layer, forming secondary isolation. The high specific surface area of the silver nanosheets in the outer silver nanosheet composite layer gives it excellent electromagnetic wave reflection capabilities, providing excellent electromagnetic shielding effects, effectively preventing interference from external electromagnetic waves, and maintaining excellent mechanical properties and wearability. The presence of the polymer isolation layer ensures that the flexibility and transmission performance of the liquid metal core are unaffected by the silver nanosheet composite layer, while also protecting the liquid metal from leakage or oxidation. The mechanical properties of the silver nanosheet composite layer support the flexible structure of the liquid metal core, preventing it from being easily damaged during dynamic use and ensuring long-term stability. The flexibility of the liquid metal and the mechanical stability of the silver nanosheets allow the fiber to adapt to the dynamic environment of human activity while remaining resistant to breakage. The synergy of signal transmission and electromagnetic shielding allows the fiber to serve as a signal carrier for wearable devices while avoiding interference from external electromagnetic waves.
[0018] Because all three layers use SEBS as the matrix or carrier, and SEBS itself has high elasticity and a low glass transition temperature, the fiber can maintain its structural integrity under the bending and stretching conditions of daily human activities, without the risk of brittleness. Furthermore, SEBS has excellent skin compatibility and breathability. The three-layer coaxial structure does not introduce any rigid components, resulting in a soft overall feel. When embedded in fabric, it does not compromise the fabric's original flexibility and breathability, fundamentally solving the problems of traditional metal shielding materials being hard, heavy, and stuffy, thus meeting the long-term wearability requirements of wearable devices. Precise material formulation and controllable manufacturing processes further ensure the stability of product performance and the feasibility of mass production. It meets the requirements for large-scale production, and the entire manufacturing process is simple with clearly defined parameters, directly adaptable to existing fiber production lines without large-scale equipment modifications, significantly lowering the industrialization threshold.
[0019] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0020] Figure 1 A schematic diagram of a scanning electron microscope for liquid metal-based electromagnetic shielding flexible coaxial fiber; Figure 2 The test results of cyclic tensile testing of liquid metal-based electromagnetic shielding flexible coaxial fiber are shown in the figure. Figure 3 The image shows the performance test results of a single tensile test on a liquid metal-based electromagnetic shielding flexible coaxial fiber. Figure 4 The figures show the electromagnetic shielding performance test results of liquid metal-based electromagnetic shielding flexible coaxial fibers. Among them, (a) is the electromagnetic shielding effectiveness analysis diagram for the 4-13 GHz band; (b) is the electromagnetic shielding effectiveness analysis diagram for the 8-16 GHz band; (c) is the electromagnetic shielding effectiveness analysis diagram for the 10-20 GHz band; and (d) is the electromagnetic shielding effectiveness analysis diagram for the 14-26 GHz band. Figure 5 The figures show the electromagnetic shielding performance test results of liquid metal-based electromagnetic shielding flexible coaxial fiber under 0-90° bending conditions. Among them, (a) is the electromagnetic shielding effectiveness analysis diagram of the 4-13GHz band; (b) is the electromagnetic shielding effectiveness analysis diagram of the 8-16GHz band; (c) is the electromagnetic shielding effectiveness analysis diagram of the 10-20GHz band; and (d) is the electromagnetic shielding effectiveness analysis diagram of the 14-26GHz band. Figure 6 The resistance change of liquid metal-based electromagnetic shielding flexible coaxial fiber under a single tensile limit state is shown in the figure. Figure 7 The graph shows the resistance variation of liquid metal-based electromagnetic shielding flexible coaxial fiber under bending conditions of 0-90°. Detailed Implementation
[0021] To better understand the above technical solutions, a detailed description of the solutions will be provided below in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0022] The terminology used in the embodiments of this invention is for the purpose of describing particular embodiments only and is not intended to limit the invention. The singular forms “a,” “the,” and “the” as used in the embodiments of this invention and the appended claims are also intended to include the plural forms, and “multiple” generally includes at least two unless the context clearly indicates otherwise.
[0023] It should also be noted that the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that an article or device that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such an article or device. Without further limitation, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the article or device that includes said element.
[0024] Example This invention provides a liquid metal-based electromagnetic shielding flexible coaxial fiber. The raw materials used in this embodiment all meet the requirements for process stability and performance reliability. Specifically, the SEBS matrix material is a styrene-ethylene-butene-styrene block copolymer (G1657) from Kraton, whose high elasticity and low glass transition temperature ensure the fiber's flexibility. The nano-silver sheets are selected with a diameter of 5-8 μm and a purity ≥99.9%. For auxiliary equipment, a drying oven is used for SEBS dehydration, an electromagnetic rotor stirrer ensures uniform material mixing, and a coaxial extrusion device equipped with 8G / 12G / 18G coaxial needles achieves layered molding.
[0025] First, dehydration of the SEBS matrix material is performed. 100g of SEBS granules are weighed and placed in a forced-air drying oven. The drying temperature is set to 50℃ and dried continuously for 10 hours to completely remove residual moisture from the material. This effectively prevents the formation of air bubbles during subsequent dissolution and blending, which could damage the three-layer coaxial structure of the fibers. After drying, the SEBS granules are quickly transferred to a desiccator to cool to room temperature to prevent reabsorption of moisture from the air during the cooling process.
[0026] Next, a SEBS solution was prepared. 30g of dehydrated SEBS particles and 90g of toluene were weighed out at a 1:3 mass ratio and poured into a glass container. The container was heated to 60°C to ensure efficient SEBS dissolution. An electromagnetic rotor was placed in the container and its speed was adjusted to 200 rpm. Stirring was then initiated and continued for 24 hours. The dissolution status was observed every 4 hours during stirring until the SEBS particles were completely dissolved, resulting in a homogeneous, transparent SEBS solution free of visible impurities or undissolved particles. The solution was then cooled to room temperature for later use to avoid the high temperature affecting the stability of subsequent blends.
[0027] Subsequently, the silver nanosheet composite material was prepared. 10 mL of the aforementioned SEBS solution was accurately measured using a pipette and poured into a 50 mL beaker. Then, 2 mL of the silver nanosheet dispersion was measured, resulting in a SEBS solution to silver nanosheet volume ratio of 5:1. The beaker was placed on a magnetic stirrer, and the stirring speed was adjusted to 200 rpm. Mechanical stirring was performed continuously for 3 minutes, gently assisting dispersion with a clean glass rod during the stirring process to ensure that the silver nanosheets were uniformly dispersed in the SEBS solution without agglomeration, ultimately yielding a composite material suspension.
[0028] Measure 5 mL of SEBS solution into a 25 mL beaker using a pipette, and then draw 5 mL of gallium-indium alloy using a syringe. At this point, the volume ratio of SEBS solution to gallium-indium alloy is 1:1. Set the stirring speed to 200 rpm and continue mechanical stirring for 5 minutes. During the stirring process, closely observe the dispersion state of the gallium-indium alloy. No obvious stratification or agglomeration is observed, and a uniform and stable liquid metal composite material is finally obtained. Store it in a sealed container for later use.
[0029] The silver nanosheet composite material, SEBS solution, and liquid metal composite material prepared above were loaded into the outer, middle, and inner barrels of a coaxial extrusion device, respectively, ensuring that each barrel was well sealed to prevent material leakage. 8G, 12G, and 18G coaxial needles were selected, and the extrusion speeds were set as follows: outer layer silver nanosheet composite material 1.6 mm / min, middle layer SEBS solution 1.5 mm / min, and inner layer liquid metal composite material 1.2 mm / min. This speed ratio ensures the uniformity of the thickness of the three-layer structure. The coaxial extrusion device was turned on, and the extrusion environment temperature was controlled at 25℃ and relative humidity at 40% to avoid the influence of temperature and humidity fluctuations on material flowability. During extrusion, the fiber appearance was observed to ensure that the initially formed coaxial fibers had a smooth surface without scratches or bubbles.
[0030] Finally, solvent evaporation curing is carried out. The pre-formed coaxial fiber is placed in a drying oven and the heating temperature is set to 60℃ to accelerate the evaporation of toluene solvent, shorten the curing time, and ensure uniform solvent evaporation. Finally, a liquid metal-based electromagnetic shielding flexible coaxial fiber with a diameter of 3.35±0.05mm is obtained.
[0031] The prepared fibers were observed using a scanning electron microscope. It was found that the final liquid metal-based electromagnetic shielding flexible coaxial fiber had a diameter of 3.35±0.05 mm and no obvious structural defects such as voids, delamination or bubbles on the surface. This proves that the preparation process can achieve stable composite of materials and provides a structural basis for the electromagnetic shielding performance and mechanical properties of the fiber.
[0032] The total electromagnetic shielding effectiveness (SE total) and reflection shielding effectiveness (SE reflection shielding effectiveness) of the fibers were tested using a vector network analyzer in the 4-26 GHz frequency band. R ) and absorption and shielding effectiveness (SE) A Test results show that in the 6GHz band, SE total = 93dB, SE A =82dB; in the 15GHz band, SE total=77dB, SE A =65dB; in the 26GHz band, SE total=58dB, SE A =48dB. Throughout the entire test frequency band, the total electromagnetic shielding effectiveness of the fiber is generally ≥40dB, higher than the industry average of 30-40dB for conventional flexible shielding fibers. It can effectively suppress power frequency interference and wireless communication radiation such as Wi-Fi, Bluetooth, and 5G. (See [reference needed]) Figure 4 As observed, some sub-maps cover a frequency range of 4-15GHz, while others extend to 10-26GHz, covering the 5G millimeter wave band and extended wireless communication bands. This completely covers wireless communication interference sources beyond power frequency interference (50Hz), such as Wi-Fi, Bluetooth, and cellular networks. No significant performance degradation was observed at frequencies below 4GHz, indicating that the fiber has no shielding blind spots within the core operating frequency band of wearable devices, thus solving the defect of traditional carbon-based shielding materials that are only suitable for low-frequency and high-frequency shielding failures.
[0033] Throughout the 4-26GHz full test frequency band, the SE total curve consistently remained above 55dB, with some high-frequency bands even reaching 80-100dB, fully meeting the core requirement of suppressing low-amplitude physiological signals (such as 0.1-5mV ECG signals) from electromagnetic interference.
[0034] like Figure 5 The figure shows the performance of the fiber after bending from 0-90° in a wide frequency range of 4-26GHz. It can be seen that the material has broadband electromagnetic shielding capability in the microwave band and can be applied to multi-band electromagnetic interference protection scenarios. The total shielding effectiveness (SEtotal) remains high across all frequency bands, ≥50dB in most bands and even approaching 90dB in some bands, indicating that the fiber provides excellent overall electromagnetic shielding after bending from 0-90° and can effectively block electromagnetic wave penetration. Absorption loss (SE) AThe presence of significant peaks in certain frequency bands indicates that the fiber has a strong ability to absorb electromagnetic waves, resulting in low reflection loss (SE). R It exhibits significant fluctuations across various frequency bands, similar to SE. A Together, they form the overall shielding effectiveness. Overall, SE total is higher than SE. R This indicates that absorption loss accounts for a larger proportion of the total shielding, and the material achieves efficient shielding through the synergistic effect of absorption and reflection. After bending from 0-90°, SE total and SE... A SE R The curve shape did not show obvious attenuation or distortion, indicating that the fiber has good bending resistance and has application potential in flexible scenarios, such as electromagnetic protection of wearable devices and flexible electronics.
[0035] In summary, this fiber maintains high electromagnetic shielding effectiveness in the 4-26GHz broadband range even after bending at 0-90°, and achieves efficient shielding through the synergistic effect of absorption and reflection. It also has good bending stability, making it suitable for flexible electromagnetic shielding applications.
[0036] The fibers were subjected to cyclic tensile tests to evaluate their mechanical flexibility and structural durability, such as... Figure 2 As shown, the mechanical properties are within the load range of -0.5 to 2N. After 10 cycles of stretching, the fiber was removed and its appearance was observed. It was found that it still maintained an intact structure without any breakage, cracking or delamination, indicating that the fiber has good structural stability. This proves that the fiber can maintain stable electromagnetic shielding performance after long-term stretching and use, meeting the needs of wearable devices for long-term contact with the human body.
[0037] A single tensile test is performed on the fiber, such as Figure 3As shown, within the strain range of 0-250%, the load on the fiber continuously increases with strain without fracture (the curve shows no significant drop or abrupt change), indicating that the fiber possesses excellent tensile ductility, capable of withstanding large tensile deformation while maintaining structural integrity, making it suitable for wearable devices that require frequent bending and stretching. In the low-strain stage, the load rapidly increases from 0 to approximately 4N, with a steep curve slope, reflecting that the fiber is dominated by elastic deformation under small deformations, with the elastic components within the material responding quickly to tensile force. In the medium-to-high strain stage, the load increase rate gradually slows down, and the curve becomes flatter, indicating that the fiber enters the viscoelastic / plastic deformation stage. At this point, irreversible slippage occurs in the SEBS matrix segments, and the interface between the liquid metal core layer and the polymer layer undergoes synergistic deformation, jointly providing continuous resistance to stretching. Furthermore, the three layers are tightly bonded, without any abrupt load changes caused by interlayer delamination. During the experiment, the fiber only experienced a load of about 6N at 250% strain, and there was no breakage or sudden drop in load throughout the process. This demonstrates the excellent interlayer bonding of the three-layer coaxial structure. During the stretching process, the inner liquid metal layer, the middle SEBS isolation layer, and the outer silver nanosheet composite layer did not undergo delamination or damage. The fiber exhibits good tensile toughness, achieving a balance between flexibility and strength. It will not lose flexibility due to excessive strength, nor will it break easily due to insufficient strength, thus meeting the dual requirements of high flexibility and tensile strength for wearable electronic fabrics.
[0038] The resistive response under the single tensile limit and the resistive stability under bending angle were tested respectively. The resistance change after the single tensile limit is as follows: Figure 6 As shown, the curve starts from R / R0=1 and shows a significant upward trend with increasing strain. When the strain approaches 500%, the relative resistance approaches 4. Within the large strain range of 0-500%, the relative resistance of the fiber shows a continuous and significant upward trend with increasing strain, indicating high sensitivity to tensile deformation. This makes it suitable for deformation detection in large strain scenarios, such as flexible sensors and strain monitoring in wearable devices. Excellent tensile tolerance: Under large strain, the resistance change shows no obvious saturation or abrupt change, demonstrating the stability and continuity of the conductive network during stretching. It can maintain a reliable electrical response under repeated large deformations, making it suitable for flexible electronic applications requiring long-term tensile deformation.
[0039] The change in resistance after bending from 0 to 90° is as follows: Figure 7 As shown, the resistance remains essentially stable within the 0-90° bending range, with a very small error bar, indicating good data repeatability. The bending diagram further illustrates that the fiber exhibits almost no change in resistance under 0-90° bending deformation, demonstrating excellent bending stability, making it suitable for applications requiring repeated bending, such as flexible electronics and wearable devices. The material exhibits excellent resistance stability during 0-90° bending, with bending deformation having virtually no effect on the resistance, demonstrating good flexible electrical reliability, and is suitable for applications such as flexible electromagnetic shielding and flexible sensors.
[0040] Therefore, this invention employs the aforementioned liquid metal-based electromagnetic shielding flexible coaxial fiber and its preparation method, resulting in a three-layer coaxial structure that exhibits a synergistic effect. The gallium-indium alloy in the inner liquid metal core layer, as a low-melting-point liquid metal, possesses excellent conductivity, not only rapidly guiding incident electromagnetic waves but also preliminarily absorbing any unguided electromagnetic waves. This adapts to the construction requirements of flexible circuits, significantly improving the structure's reliability and applicability. The SEBS in the middle polymer isolation layer, as a flexible insulating polymer, avoids conductive interference caused by direct contact between the inner liquid metal and the outer silver nanosheet composite layer, and also blocks some electromagnetic waves penetrating the inner layer, forming secondary isolation. The high specific surface area of the silver nanosheets in the outer silver nanosheet composite layer gives it excellent electromagnetic wave reflection capabilities, providing superior electromagnetic shielding, effectively preventing interference from external electromagnetic waves, and maintaining excellent mechanical properties and wearability. The presence of the polymer isolation layer ensures that the flexibility and transmission performance of the liquid metal core are unaffected by the silver nanosheet composite layer, while also protecting the liquid metal from leakage or oxidation. The mechanical properties of the silver nanosheet composite layer support the flexible structure of the liquid metal core, preventing it from being easily damaged during dynamic use and ensuring long-term stability. The flexibility of the liquid metal and the mechanical stability of the silver nanosheets allow the fiber to adapt to the dynamic environment of human activity while remaining resistant to breakage. The synergy of signal transmission and electromagnetic shielding allows the fiber to serve as a signal carrier for wearable devices while avoiding interference from external electromagnetic waves.
[0041] Because all three layers use SEBS as the matrix or carrier, and SEBS itself has high elasticity and a low glass transition temperature, the fiber can maintain its structural integrity under the bending and stretching conditions of daily human activities, without the risk of brittleness. Furthermore, SEBS has excellent skin compatibility and breathability. The three-layer coaxial structure does not introduce any rigid components, resulting in a soft overall feel. When embedded in fabric, it does not compromise the fabric's original flexibility and breathability, fundamentally solving the problems of traditional metal shielding materials being hard, heavy, and stuffy, thus meeting the long-term wearability requirements of wearable devices. Precise material formulation and controllable manufacturing processes further ensure the stability of product performance and the feasibility of mass production. It meets the requirements for large-scale production, and the entire manufacturing process is simple with clearly defined parameters, directly adaptable to existing fiber production lines without large-scale equipment modifications, significantly lowering the industrialization threshold.
[0042] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A liquid metal-based electromagnetic shielding flexible coaxial fiber, characterized in that, The flexible coaxial fiber has a three-layer coaxial structure, consisting of a liquid metal core layer, a polymer isolation layer, and a silver nanosheet composite layer from the inside out. The liquid metal core layer is made of a liquid metal composite material formed by blending SEBS solution with gallium indium alloy and then curing it through solvent evaporation. The polymer isolation layer is composed of an SEBS matrix formed by completely evaporating the SEBS solution with toluene. The silver nanosheet composite layer is made of a silver nanosheet composite material formed by blending SEBS solution with silver nanosheets and then curing it through solvent evaporation. The overall diameter of the flexible coaxial fiber is 3.35 ± 0.05 mm.
2. A method for preparing liquid metal-based electromagnetic shielding flexible coaxial fiber as described in claim 1, characterized in that, Includes the following steps: S1. Prepare SEBS matrix material. Place the SEBS matrix material in a dry environment and dry it for 10 hours to remove residual moisture from the material and avoid bubbles from forming during subsequent dissolution and blending processes. S2. Add the dehydrated SEBS matrix material from step S1 and toluene into a container, place the container at 60°C, and stir continuously with a stirring device until the SEBS particles are completely dissolved to obtain a SEBS solution. S3. Take the SEBS solution obtained in step S2 and mix it with the silver nanosheets. Then, mechanically stir and blend the mixture to obtain a silver nanosheet composite material with uniformly dispersed silver nanosheets. S4. Take the SEBS solution obtained in step S2 and mix it with gallium indium alloy. Mechanically stir and blend the mixture to obtain a liquid metal composite material with uniformly dispersed gallium indium alloy. S5. The silver nanosheet composite material obtained in step S3, the SEBS solution obtained in step S2, and the liquid metal composite material obtained in step S4 are respectively fed into a coaxial extrusion device to extrude and obtain pre-formed coaxial fibers. S6. The coaxial fiber initially formed in step S5 is heated in an environment of 60°C to accelerate the evaporation of toluene solvent. After the solvent has completely evaporated, liquid metal-based electromagnetic shielding flexible coaxial fiber is obtained.
3. The method for preparing a liquid metal-based electromagnetic shielding flexible coaxial fiber according to claim 2, characterized in that, The drying environment described in step S1 is a drying oven, and the temperature inside the drying oven is controlled between room temperature and 60°C.
4. The method for preparing a liquid metal-based electromagnetic shielding flexible coaxial fiber according to claim 2, characterized in that, The mass ratio of the SEBS matrix material to toluene in step S2 is 1:
3.
5. The method for preparing a liquid metal-based electromagnetic shielding flexible coaxial fiber according to claim 2, characterized in that, During step S2, the stirring speed is controlled at 150-300 rpm, and stirring is continued for 24 hours to ensure that the SEBS particles are fully dissolved and the solution is uniform.
6. The method for preparing a liquid metal-based electromagnetic shielding flexible coaxial fiber according to claim 2, characterized in that, In step S3, the volume ratio of the SEBS solution to the silver nanosheets is 5:1, and the diameter of the silver nanosheets is 5-10 micrometers.
7. The method for preparing a liquid metal-based electromagnetic shielding flexible coaxial fiber according to claim 2, characterized in that, The mechanical stirring and mixing in step S3 lasts for 3 minutes, and the stirring speed is 180-220 rpm to avoid agglomeration of the silver nanosheets.
8. The method for preparing a liquid metal-based electromagnetic shielding flexible coaxial fiber according to claim 2, characterized in that, In step S4, the volume ratio of SEBS solution to gallium-indium alloy is 1:
1.
9. The method for preparing a liquid metal-based electromagnetic shielding flexible coaxial fiber according to claim 2, characterized in that, The duration of mechanical stirring and mixing in step S4 is 5 minutes, and the stirring speed is 180-220 rpm.
10. The method for preparing a liquid metal-based electromagnetic shielding flexible coaxial fiber according to claim 2, characterized in that, In step S5, the extrusion speed of the coaxial extrusion device is 1.2-1.6 mm / min.
Citation Information
Patent Citations
Coaxial conductive elastic composite filament and preparation method thereof
CN105648555A
Liquid metal fiber / elastomer flexible composite material as well as preparation method and application thereof
CN113527733A